2014
DOI: 10.5935/1678-9741.20140016
|View full text |Cite
|
Sign up to set email alerts
|

Information technology implementing globalization on strategies for quality care provided to children submitted to cardiac surgery: International Quality Improvement Collaborative Program – IQIC

Abstract: IntroductionCongenital heart diseases are the world's most common major birth defect, affecting one in every 120 children. Ninety percent of these children are born in areas where appropriate medical care is inadequate or unavailable.ObjectiveTo share knowledge and experience between an international center of excellence in pediatric cardiac surgery and a related program in Brazil.MethodsThe strategy used by the program was based on long-term technological and educational support models used in that center, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Mortality also decreased almost by half, but it did not reach statistical significance. Moreover, Sciarra et al [ 3 ] reported that implementation of initiatives such as IQIC is feasible in our region, improving the quality of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality also decreased almost by half, but it did not reach statistical significance. Moreover, Sciarra et al [ 3 ] reported that implementation of initiatives such as IQIC is feasible in our region, improving the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…This is because they help to target reasons for such variations and to find solutions for shared problems. In fact, joining a collaborative quality improvement program has proved beneficial in different countries [ 1 - 3 ] . Other advantages of joining such programs are improvements in long-term survival and better use of resources.…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative quality improvement programs have improved health care quality in many different scenarios because they help target reasons for such variations and find solutions for shared problems. Joining a coordinated quality improvement program has proved beneficial in other countries [ 35 - 37 ] .…”
Section: Pediatric Cardiac Surgery In the Brazilian Public Health Car...mentioning
confidence: 99%
“…Globalisation has been however extended much further, by policies that have opened economies domestically and internationally. This has been aided by technological innovations that have enhanced the speed and simplicity of communication and dramatically increased exchanges of knowledge and resources across the globe (Sciarra et al 2014). There are now fewer obstacles to the mobility of products and services across national borders (Dalmolin et al 2013).…”
Section: Introductionmentioning
confidence: 99%